Work Motivators for Members of Generation Z: A Quantitative Research in Poland - Wiesław LUKASINSKI; Sabina MROWKA (Communications of International Proceedings, 2025)
The competitiveness of a modern organisation is determined by the attitudes and behaviours of its employees. The effective achievement of set goals is possible thanks to the commitment of the people employed in the organisation, which is why it is particularly important to identify the factors that motivate them to perform their duties. A review of the literature reveals a lack of research on the work motivators of Generation Z in Poland. These are people who are currently entering the job market and who have significantly greater digital skills than previous generations. This is particularly valuable in Industry 4.0. The aim of this article is to identify key motivators for work among employees from the perspective of surveyed members of Generation Z in Poland. This was achieved through a literature review, a survey, statistical analysis and interpretation of obtained results. The limitations of the research were the deliberate selection of the sample, which included only students or graduates of economics programmes in Poland who were representatives of Generation Z. Such a sample selection limits the possibility of generalising the conclusions to the entire population. Based on the results obtained, it can be concluded that the following factors are particularly important for the members of Generation Z surveyed: a friendly atmosphere at work, good relations between employees, and opportunities for self-fulfilment. They place great importance not only on transparency of the remuneration system, career development paths, and promotion opportunities, but also on freedom of action, praise, and recognition from their superiors.
Keywords: motivation; motivating to work; motivators for Generation Z